Cardioprotective Effects of Piperlongumine against Doxorubicin-Induced Myocardial Infarction via Down-Regulating Cardiac Biomarkers in Rats - Xiong, Guo (Indian Journal of Pharmaceutical Education and Research)
Background: Doxorubicin, an extensively utilized antineoplastic agent, has been a significant contributor to the remarkable advancements in cancer treatment over the past several decades. However, the clinical usefulness of this powerful drug is often restricted by its well-documented cardiotoxic effects. Objectives: The present research work was focused at unveiling the therapeutic roles of piperlongumine against doxorubicin-induced cardiotoxicity. Materials and Methods: The experimental rats were received 2.5 mg/kg of doxorubicin to induce cardiotoxicity, subsequently treated with 50 mg/kg of piperlongumine. Plethysmography via the tail-cuff was employed to assess hemodynamic parameters. The oxidative and antioxidative biomarkers, and cardiac function markers, were quantified using a commercial assay kits. The concentrations of inflammatory biomarkers and apoptotic proteins were also assessed using the kits. Results: The piperlongumine treatment considerably enhanced the heart and body weights of the doxorubicin-induced rats. The piperlongumine treatment significantly lowered the hemodynamic parameters in rats with doxorubicin-induced cardiotoxicity. Furthermore, the piperlongumine treatment markedly reduced the activities of cardiac function markers and inflammatory biomarkers in the doxorubicin-induced rats. Conclusion: The present findings exhibited that piperlongumine can mitigate the biochemical and cardiotoxic effects induced by doxorubicin in rats via its robust antioxidant and anti-inflammatory effects. Thus, piperlongumine may serve as an novel treatment option in conjunction with doxorubicin to mitigate its cardiotoxic effects.
Keywords: Cardiotoxicity; Piperlongumine; Cardiomyocytes; Hemodynamic markers; Heart weight.